Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This chapter reviews developments in GDP over the past several decades. The analysis shows that accumulation of labor and capital explains the bulk of overall output growth since 1990, with changes in total factor productivity playing only a minor role. Moreover, while increases in total factor productivity (TFP) during 1990-2009 have been close to the worldwide average, the pace of TFP growth fell during the 2000s. This suggests scope for increasing the efficiency of factor markets and highlights the importance of recent reforms to promote knowledge-based activity.